Edukasi Kesehatan tentang Personal Hygiene pada Peserta Didik Sekolah Dasar di Kota Manado - Sumampouw, Oksfriani Jufri; Nelwan, Jeini Ester (Nawasena Bhakti, 2025)
Background: Schools are places where health education on important aspects of hygiene, environment and sanitation, and social habits are provided. Health is a key factor in school entry, as well as sustained participation and achievement in school. The purpose of this activity is to provide health education about Personal Hygiene to Elementary School Students. Methods: The Community Service Team (CoS) conducted activities with the theme of personal hygiene education for students in elementary schools. The method of implementation in this CoS activity is the counseling method to students at the 107 Manado State Elementary School. This activity was carried out in September 2024 at 08.00-complete. CoS activities are carried out by delivering personal hygiene material using videos and role play. The targets in this activity are students. Results: The results of this activity showed student enthusiasm and knowledge about personal hygiene. As a follow-up action, a school personal hygiene team was formed consisting of teachers and students who served as cadres/ officers driving personal hygiene practices at school. Conclusions: This CoS activity provides an understanding to elementary school students about personal hygiene that must be done through health education with counseling.